Indigeneity in real time : the digital making of Oaxacalifornia - Kummels, Ingrid (Rutgers University Press, 2023)
"Long before the COVID-19 crisis, Mexican Indigenous peoples were faced with organizing their lives from afar, between villages in the Oaxacan Sierra Norte and the urban districts of Los Angeles, as a result of unauthorized migration and the restrictive border between Mexico and the United States. By launching cutting-edge Internet radio stations and multimedia platforms and engaging as community influencers, Zapotec and Ayuujk peoples paved their own paths to a transnational lifeway during the Trump era. This meant adapting digital technology to their needs, setting up their own infrastructure, and designing new digital formats for re-organizing community life in all its facets-including illness, death and mourning, collective celebrations, sport tournaments, and political meetings-across vast distances. Author Ingrid Kummels shows how mediamakers and users in the Sierra Norte villages and in Los Angeles created a transborder media space and aligned time regimes. By networking from multiple places, they put into practice a communal way of life called Comunalidad and an indigenized American Dream-in real time"-- Provided by publisher.
Keywords: Zapotec Indians -- California -- Los Angeles -- Social conditions.; Zapotec Indians -- Mexico -- Sierra Norte (Oaxaca) -- Social conditions.; Mixe Indians -- California -- Los Angeles -- Social conditions.; Mixe Indians -- Mexico -- Sierra Norte (Oaxaca) -- Social conditions.; Internet and Indigenous peoples -- California -- Los Angeles.; Internet and Indigenous peoples -- Mexico -- Sierra Norte (Oaxaca); Communication and culture -- California -- Los Angeles.; Communication and culture -- Mexico -- Sierra Norte (Oaxaca); Transnationalism.; Urban Zapotec Indians -- California -- Los Angeles.; Sierra Norte (Oaxaca, Mexico) -- Social life and customs.; Zapotèques -- Californie -- Los Angeles -- Conditions sociales.; Zapotèques -- Mexique -- Sierra Norte (Oaxaca) -- Conditions sociales.; Internet et autochtones -- Californie -- Los Angeles.; Internet et autochtones -- Mexique -- Sierra Norte (Oaxaca); Communication et culture -- Californie -- Los Angeles.; Communication et culture -- Mexique -- Sierra Norte (Oaxaca); Transnationalisme.; SOCIAL SCIENCE / Ethnic Studies / American / Hispanic American Studies.; SOCIAL SCIENCE / Media Studies.; SOCIAL SCIENCE / General; Communication and culture; Internet and indigenous peoples; Manners and customs; Mixe Indians -- Social conditions; Transnationalism; Urban Zapotec Indians; Zapotec Indians -- Social conditions; California -- Los Angeles; Mexico -- Sierra Norte (Oaxaca); california, mexican, latino, latina, latinx, Hispanic, immigration, migration, emigration, expat, undocumented, illegal immigration, Oaxaca, oaxacan, Zapotec, Ayuujk, indigenous, native, sierra norte, race, ethnicity, culture, racism, xenophobia, discrimination, anthropology.; Electronic books.